2022
DOI: 10.3389/fcvm.2022.1079046
|View full text |Cite
|
Sign up to set email alerts
|

Neoatherosclerosis prediction using plaque markers in intravascular optical coherence tomography images

Abstract: IntroductionIn-stent neoatherosclerosis has emerged as a crucial factor in post-stent complications including late in-stent restenosis and very late stent thrombosis. In this study, we investigated the ability of quantitative plaque characteristics from intravascular optical coherence tomography (IVOCT) images taken just prior to stent implantation to predict neoatherosclerosis after implantation.MethodsThis was a sub-study of the TRiple Assessment of Neointima Stent FOrmation to Reabsorbable polyMer with Opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Considering the diffuse inflammatory nature of atherosclerosis, it is crucial to analyze the entire 3D lesion, specifically focusing on FC surface area. In another study, we also observed that FC surface area was a strong indicator for predicting the development of neo-atherosclerosis 64 . In contrast, no assessment of thin cap was a strong predictor of MACE.…”
Section: Discussionmentioning
confidence: 68%
“…Considering the diffuse inflammatory nature of atherosclerosis, it is crucial to analyze the entire 3D lesion, specifically focusing on FC surface area. In another study, we also observed that FC surface area was a strong indicator for predicting the development of neo-atherosclerosis 64 . In contrast, no assessment of thin cap was a strong predictor of MACE.…”
Section: Discussionmentioning
confidence: 68%